Caffeine's Vascular Mechanisms of Action - Darío Echeverri; Félix R. Montes; Mariana Cabrera; Angélica Galán; Angélica Prieto (International Journal of Vascular Medicine)
Caffeine is the most widely consumed stimulating substance in the world. It is found in coffee, tea, soft drinks, chocolate, and many medications. Caffeine is a xanthine with various effects and mechanisms of action in vascular tissue. In endothelial cells, it increases intracellular calcium stimulating the production of nitric oxide through the expression of the endothelial nitric oxide synthase enzyme. Nitric oxide is diffused to the vascular smooth muscle cell to produce vasodilation. In vascular smooth muscle cells its effect is predominantly a competitive inhibition of phosphodiesterase, producing an accumulation of cAMP and vasodilation. In addition, it blocks the adenosine receptors present in the vascular tissue to produce vasoconstriction. In this paper the main mechanisms of action of caffeine on the vascular tissue are described, in which it is shown that caffeine has some cardiovascular properties and effects which could be considered beneficial.